The Local Wisdom on Sundanese People in Relationship with the Natural Environment: An Analytical Study of the Philosophy of Society of Kampung Dukuh Garut - Nasir, Malki Ahmad; Arif, Muhammad Fauzi; Safrudin, Irfan; Sholeh, N. Sausan Muhammad (KnE Social Sciences, 2023)
There is no doubt that the advent of Islam in the Archipelago Region, particularly in the Sunda World, has transformed the weltanschauung of the local community, shifting from a polytheistic paradigm to the monotheistic paradigm (tawhid). This has fostered a synergy between the outcomes of Divine revelation and Sundanese wisdom, giving rise to local wisdom in Malay-Islamic society. Moreover, the role of intellectuals in bridging the perspectives of ”sky idealism” with ”earth/cultural reality” is crucial in shaping dynamic, relevant, and applicable teachings of local wisdom embraced by the Sundanese people. This reciprocal process is evident in the collection of Sundanese local wisdom in Alam Parahyangan, whether in written form or through actions and practices. The objective of this study is to highlight several points. Firstly, it aims to demonstrate that the awareness of living in harmony with nature is manifested in the local wisdom of indigenous peoples through their views and concepts. Secondly, it seeks to emphasize the unique construction and formulation of Sundanese local wisdom, which results from the synthesis of Islamic values and Sundanese thought. Lastly, the study proposes the re-examination of Sundanese manuscripts, which serve as repositories of local Sundanese-Islamic wisdom. These manuscripts exhibit various forms of thoughts, including rhymes, dangding (a form of Sundanese poetry), advice, and others. Keywords: the local wisdom of Sundanese people, natural preservation, Sundanese text